2002
DOI: 10.2337/diacare.25.6.984
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of a Risk Score in Predicting Undiagnosed Hyperglycemia

Abstract: OBJECTIVE -Type 2 diabetes is a serious disease that is commonly undetected and for which screening is sometimes advocated. A number of risk factors are associated with prevalent undiagnosed diabetes. The use of routinely available information on these factors has been proposed as a simple and effective way of identifying individuals at high risk for having the disease. The objective of this study was to assess the effectiveness of the Cambridge risk score in a large and representative population. RESEARCH DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 31 publications
4
69
1
2
Order By: Relevance
“…In cross-sectional studies conducted in the USA and Europe, prediction models based on clinical information and lifestyle-related factors have appeared to be useful for identifying undiagnosed diabetes cases and high HbA 1c levels in screening populations [7,8,38,39]. For example, the Cambridge model has been applied successfully to identify individuals with high HbA 1c levels [9,10]. In addition, a recent cohort study showed that the Cambridge model was useful for identifying individuals with a higher [3], PROCAM [30], San Antonia [13] and Framingham models [5], were developed to predict incident diabetes in different populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cross-sectional studies conducted in the USA and Europe, prediction models based on clinical information and lifestyle-related factors have appeared to be useful for identifying undiagnosed diabetes cases and high HbA 1c levels in screening populations [7,8,38,39]. For example, the Cambridge model has been applied successfully to identify individuals with high HbA 1c levels [9,10]. In addition, a recent cohort study showed that the Cambridge model was useful for identifying individuals with a higher [3], PROCAM [30], San Antonia [13] and Framingham models [5], were developed to predict incident diabetes in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…The standard-error estimates and the confidence intervals were obtained based on 1,000 bootstrap samples. Finally, we compared the performance of the proposed prediction model with that of various prediction models derived from other populations, including Cambridge [8][9][10], Prospective Cardiovascular Münster (PROCAM) [30], San Antonia [13,14] and Framingham [5]. AUC was used to compare the discriminatory capabilities of these models and our simple points model.…”
Section: Measurement Of Biochemical Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Age constitutes a factor of independent predictive value for chronic illnesses, and is also used as a parameter to classify a person's risk for the development of nondiagnosed hyperglycemia (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sesuai dengan teori yang mengatakan bahwa mereka dengan usia lebih dari 45 tahun adalah kelompok usia yang berisiko menderita DM.8 Lebih lanjut dikatakan bahwa DM merupakan penyakit yang terjadi akibat penurunan fungsi organ tubuh (degeneratif) terutama gangguan organ pangkreas dalam menghasilkan hormon insulin, sehingga DM akan meningkat kasusnya sejalan dengan pertambahan usia. 9 Hasil penelitian ini sejalan dengan penelitian sebelumnya di Jakarta 10 dan di Padang 11 , menunjukkan bahwa kelompok umur 50-60 tahun (di atas 45 tahun) adalah kelompok yang terbanyak menderita DM dibanding kelompok umur di bawahnya. Angka kasus DM akan meningkat sesuai dengan pertambahan usia.…”
Section: Pendahuluanunclassified